The case for a sociology of dying, death, and bereavement. Issue 3 (15th March 2016) - Thompson, Neil; Allan, June; Carverhill, Philip A.; Cox, Gerry R.; Davies, Betty; Doka, Kenneth; Granek, Leeat; Harris, Darcy; Ho, Andy; Klass, Dennis; Small, Neil; Wittkowski, Joachim
ABSTRACT: Dying, death, and bereavement do not occur in a social vacuum. How individuals and groups experience these phenomena will be largely influenced by the social context in which they occur. To develop an adequate understanding of dying, death, and bereavement we therefore need to incorporate a sociological perspective into our analysis. This article examines why a sociological perspective is necessary and explores various ways in which sociology can be of practical value in both intellectual and professional contexts. A case study comparing psychological and sociological perspectives is offered by way of illustration.